Patterns of Religious Behavior and Social Interaction: The Impact of Creed Polarization in Sumber Karya Subdistrict, East Binjai - Wardani, Ella; UR, Syukri; Damanik, Nurliana (Getpress Management Journals, 2024)
The polarization of creeds has become a significant phenomenon in the religious life of modern society. This article investigates the impact of creed polarization on religious behavior patterns, social interactions and social harmony in Sumber Karya Subdistrict, East Binjai. Qualitative research methods with a field study approach were used to collect data through in-depth interviews and content analysis. The research results show that creed polarization influences variations in people's religious understanding and practices. Tensions between religious communities also arise as a result of these differences in understanding. Social media plays an important role in disseminating religious information, but is also vulnerable to the spread of polarizing content. The implications of creed polarization include a decline in the quality of religious discussion and changes in patterns of religious behavior. Recommendations are put forward to overcome the polarization of the Aqidah, including the promotion of inclusive religious dialogue and a deeper understanding of religious differences. It is hoped that these steps can strengthen social harmony and harmony between religious communities in society.